2020
DOI: 10.1016/j.pharmthera.2019.107454
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on targeting PIM kinases to overcome mechanisms of drug resistance and immune evasion in cancer

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 172 publications
1
29
0
Order By: Relevance
“…c-MYC is also upregulated by both PIM and mTOR 6 . This relationship gives rise to the development of resistance to treatment, as the pathways can bypass the inhibition by compensating for loss of signalling of either one 12 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…c-MYC is also upregulated by both PIM and mTOR 6 . This relationship gives rise to the development of resistance to treatment, as the pathways can bypass the inhibition by compensating for loss of signalling of either one 12 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Our results prove that PIM-1 may function as an oncogene in CC, and PIM-1 may exert its carcinogenic effects through activating the EGFR signaling via increasing the proliferation and decreasing the apoptosis of CC cells. The PIM kinases were first reported as most significantly up-regulated genes during the process of embryonic development 9,15 ; however, in recent years, PIMs were also found to be over-expressed in several cancers. The role of PIM-1 as an oncogene has been investigated in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…The PIM kinase family is comprised of three proteins, including PIM-1, PIM -2, and PIM-3. 9 It has been reported that different transcription factors can recruit PIM-1 to the…”
Section: Introductionmentioning
confidence: 99%
“…The Proviral integration site for Moloney murine leukemia virus (PIM) kinases are a family of serine-threonine kinases that are known to promote tumorigenesis by impacting cell cycle progression, survival, and proliferation (Malone et al, 2020; Nawijn et al, 2011). Pim1 expression is elevated in ~50% of human prostate cancer specimens, particularly in high Gleason grade and aggressive metastatic prostate cancer cases, highlighting its ability to enhance tumorigenesis (Chen et al, 2005; Dhanasekaran et al, 2001).…”
Section: Introductionmentioning
confidence: 99%